(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Summary: Amiodarone, a drug that treats arrhythmias induces pulmonary toxicity through interplay between oxidative stress and inflammation. Quercetin, a flavonoid widely occurring in natural products possesses antioxidant and anti-inflammatory properties. The aim of the present study was to evaluate the effects of quercetin on pulmonary responses in rats after amiodarone intra-tracheal instillation. Eighteen female Wistar rats (150-250 g) were randomly assigned into three groups of six animals each namely; control, amiodarone (AMI) and amiodarone + Quercetin (AMI + Quercetin) groups. AMI group received 2 intra-tracheal instillations of amiodarone (6.25mg/kg in 0.3ml of water) on days 0 and 2 and 0.4ml of 2% DMSO (Dimethyl sulfoxide) orally from day 0 for 3 weeks. AMI + Quercetin group was administered 2 intratracheal instillations of amiodarone on days 0 and 2 and 20mg/kg body weight of quercetin in 2% DMSO from day 0 for 3 weeks. Thereafter, the animals were sacrificed and bronchoalveolar lavage fluid (BALF) was collected to determine total cell polymorphonuclear (PMN) cell and macrophage counts. Inflammation of the lung tissues was also assessed. Macrophage count of AMI + Quercetin group was significantly lowered (p<0.01) compared to AMI group. Inflammation rate of the AMI + Quercetin group was significantly reduced compared to AMI group (p<0.01). Quercetin treatment markedly suppressed amiodarone induced toxicity in the pulmonary tissues.